Developing English Learning Materials Integrated with Problem-Based Learning for Vocational Fashion Schools Students: An ESP Context - Lubis, Siti Isma Sari; Yudistira, Sukma; Saputra , Indra (Journal of Language and Literature Studies, 2025)
This research relates to how the English materials are developed for fashion students of SMK based on Problem Based Learning Approach. This research aims to develop the English materials by applied the ESP based on need analysis of the students. It is done in order to fulfill the needs of fashion students of SMK Negeri 6 PadangResearch and development (R&D) by Borg and Gall, which comprises ten research processes, is the methodology used in this article. Pre-development, development, validation, revision, and product testing are the five primary cycles in which those phases are altered in this study. Questionnaires and document analysis are the methods used to acquire data. The students, the English instructor, the head of the fashion department, the fashion students’ alumni, the education and ESP specialist, and the current syllabus and materials are the sources of the data. Students’ grades increase as a result of testing the content. In the pre-test, the students’ average score was 52.6. Meanwhile, the average student post test score was 64.8. There were 20 students who passed the standard minimum whereas previously only 8 students passed the standard minimum. After being given a post-test, several students were also asked for their comments about the new reading material. Everyone agreed and said that this new reading material was more interesting and suited to students’ needs. It means that using PBL approach and need analysis in developing English material can increase the students’ achievement in learning English.